Making Oxalic Acid From Palm Oil Pelepah (Elaeis Guineensis) Through Nitric Acid Oxidation Reaction - Ihwan Rahmadi (Jurnal Matematika Dan Ilmu Pengetahuan Alam LLDikti Wilayah 1 (JUMPA), 2021)
Palm oil palm is one of the solid waste produced by oil palm plantations every harvest. Chemical analysis of palm oil palm oil pellets showed that there are components of cellulose, hemiscellulose, and lignin that show that palm oil pellets have the opportunity to be further processed into useful and economically valuable products. Palm waste contains cellulose by 34.89%, hemiscellulose by 27.14%, and lignin by 19.87%. The analysis conducted on raw materials includes the analysis of water content and cellulose levels of palm oil palm oil. 46.6% and cellulose levels of 29.2%. In this study quantitative analysis was conducted in the form of cellulose conversion and oxalic acid yield. The largest cellulose conversion was obtained at the use of 70% nitric acid concentration and 80 minutes reaction time of 58.56%.